2003
DOI: 10.1046/j.1445-6664.2003.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of direct dry seeding on rainfed paddy vegetation in north‐east Thailand

Abstract: In north‐east Thailand where rainfed paddy cultivation is commonplace, direct dry seeding is replacing transplanting to increase the frequency of successful plantings and to save labor. The present study shows the impact of this change on paddy vegetation from agricultural and ecological viewpoints. One hundred and seventy‐nine paddy fields from a wide range of climatic, topography, soil and hydrological conditions were used in this study. Authors visited these fields every 3 weeks during the rainy seasons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Our study suggested that higher usage rates apply in the Kamping Puoy Irrigation Rehabilitation Area. As shown in rain‐fed paddy fields in north‐eastern Thailand (Tomita et al . 2003a,b), the rain‐fed fields in higher topographic positions with less water availability (the rain‐fed upslope group) recorded lower percentages of sedges (61% in 2006) and higher percentages of broad‐leaved weeds (39% in 2006).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our study suggested that higher usage rates apply in the Kamping Puoy Irrigation Rehabilitation Area. As shown in rain‐fed paddy fields in north‐eastern Thailand (Tomita et al . 2003a,b), the rain‐fed fields in higher topographic positions with less water availability (the rain‐fed upslope group) recorded lower percentages of sedges (61% in 2006) and higher percentages of broad‐leaved weeds (39% in 2006).…”
Section: Discussionmentioning
confidence: 61%
“…As the number of rain‐fed fields that was surveyed was relatively small, we could not judge whether or not the weed seed banks differed between the fields in the higher (upslope group) and lower (downslope group) topographic positions. Tomita et al . (2003a,b,c) showed that fields in higher topographic positions had more weed vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of the soil seed bank is another important aspect in changes of weed vegetation. Unlike the influence of past cultivating methods on species diversity and productivity (Tomita et al . 2003), species composition was affected by the methods in the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work (Tomita et al . 2003) revealed paddy vegetation was largely influenced by disturbance intensity such as land preparation and resource availability.…”
Section: Introductionmentioning
confidence: 99%
“…alluvial flood plains of several tributaries of the Mekong River and low surfaces of undulating plains, rice is produced in paddy fields, whereas in higher undulating plains, upland field crops, such as cassava, sugarcane and kenaf, are produced. At present, although rapid economic development is accelerating agricultural production changes, including the extension of direct seeding technology in paddy production (Tomita et al, 2003) and expansion of sugarcane producing areas into lowlands, the basic patterns of agricultural land use have not changed significantly. Paddy fields are distributed all over Northeast Thailand, whereas sugarcane fields are mainly distributed in the northwestern (Udon Thani, Khon Kaen and Chayapum Provinces), southwestern (Nakorn Rachasima Province) and the middle eastern parts (Muk Dahan Province) of this area, mainly because of the location of sugar processing factories.…”
Section: Discussionmentioning
confidence: 99%